Neuro-Educational Data Mining: Bridging Brain-Computer Interfaces and Predictive Learning Analytics for Personalized Instruction - Catur Lestari Wijayanti (Yayasan Adra Karima Hubbi, 2026)
Background. Rapid transformations in labor markets driven by digitalization and platform-based employment have reshaped traditional career trajectories, particularly among Generation Z. Emerging gig economy structures require adaptive competencies that extend beyond conventional career preparation, yet many career development models remain oriented toward stable, long-term employment pathways. Purpose. This study aimed to examine the role of career counseling in enhancing Generation Z’s readiness for gig economy participation. Specifically, it investigated the extent to which career adaptability, digital career competence, entrepreneurial readiness, and career self-efficacy contribute to preparedness for non-traditional and platform-based employment. Method. A mixed-methods sequential explanatory design was employed. Quantitative data were collected from 450 participants using validated instruments measuring career adaptability, digital career competence, entrepreneurial readiness, career self-efficacy, and gig economy career readiness. Structural Equation Modeling (SEM) was applied to test the relationships among variables. Qualitative interviews were conducted to deepen understanding of participants’ perceptions of career counseling experiences and alternative career pathways. Results. The findings indicate that career counseling has a significant positive effect on all examined variables. Career adaptability emerged as the strongest predictor of gig economy readiness, followed by digital career competence and entrepreneurial readiness. Career self-efficacy also contributed significantly to readiness outcomes. The qualitative data supported these findings by showing that students who experienced structured career guidance demonstrated greater confidence in navigating uncertain and project-based labor markets. However, some participants still exhibited limited awareness of gig economy risks and unstable income structures, indicating uneven preparedness. Conclusion. The study highlights that career counseling plays a critical role in preparing Generation Z for evolving labor market demands. Strengthening adaptive, digital, and entrepreneurial dimensions within counseling frameworks is essential for improving readiness for gig and platform-based employment. These findings suggest that traditional career guidance models require substantial redesign to align with the realities of contemporary work ecosystems.